MARKET ANALYSIS OF ENGINEERING SERVICES IN POWER INDUSTRY - Y. Aleksandrov (Вестник университета)
In the context of the implementation of the strategy of modernization of the electric power industry plays an important role in the development of the engineering business that is in a stage of formation and development. It is shown that in recent years in the market of engineering services in power industry, there are many new players that significantly exacerbated competition in this business. Analyzed the main spheres of engineering activity for the company JSC «VTI».